Playing e-sport among university students: benefits and disadvantages / Nurul Nadiah Rasdi and Ahmad Najmie Rusli - Rasdi, Nurul Nadiah; Rusli, Ahmad Najmie (Universiti Teknologi MARA, Kedah, 2021)
E-sport or electronic sport is a competitive video gaming, where people play against each other online. Other people can watch and it will usually involve cash prizes. As students also play e-sport, it is crucial to know students' opinions on e-sport. So, this study is conducted with the aim to investigate university students' opinions on the benefits and disadvantages of playing e-sport. Questionnaires were distributed to 66 respondents and data gathered was analysed using SPSS 20.0. The findings revealed that playing e-sport benefited the students in terms of they felt happy (mean=4.18), they connected to friends (mean=4.03), and it promoted teamwork (mean=3.97). Meanwhile, the disadvantages of playing e-sport were they felt tired and sleepy (mean=3.58), they had eye fatigue (mean=3.50), and they had neck and back pain (mean=3.33).